Strategies for Improving Population Administration Services at the Tuban District Population and Civil Registration Office - Romadhona, Lusyana Desi; Kriswibowo, Arimurti (Universitas Muhammadiyah Ponorogo, 2025)
The Tuban District Population and Civil Registration Office (Dispendukcapil) has an obligation under the law to organize population administration services as an integral part of public services that must be accounted for by the government to the community. However, a number of obstacles are still faced in the administration of civil registration services. The purpose of this research is to investigate and describe strategies that can be applied to improve civil registration services at the Tuban District Dispendukcapil. The research method used was a qualitative approach using a case study. Three data collection techniques were used: documentation, observation and interviews. A purposive and snowball approach was used to identify relevant informants. The data analysis process followed an interactive approach, with the stages of Data Collection, Data Condensation, Data Display, and Conclusion Drawing and Verification, developed by Miles & Huberman. This research, which adopted Moenir's theoretical framework, produced several findings, including that 1) the awareness of officials and executive leaders regarding the problem has made significant progress; 2) The process of making adequate regulations has run quite smoothly, but in terms of SOPs, the completion it is still not ideal; 3) Although the organization has a dynamic system mechanism, there are still shortcomings in socialization to the community; 4) The competencies and talents required for a job or position have been applied, and everything is going well; and 5) Service facilities are available in accordance with the nature and format of service tasks, but the‘ball pick-up’ services still need to be improved.